Neurologic manifestations of Long COVID in Colombia: a comparative analysis of post-hospitalization vs. non-hospitalized patients - Hurtado, Carolina; Rojas-Gualdrón, Diego Fernando; Pérez Giraldo, Gina S.; Villegas Arbelaez, Esteban; Mantilla, Salvador Ernesto Medina; Campuzano-Sierra, Mariana; Ospina-Patino, Santiago; Arroyave-Bustamante, Mariana; Uribe-Vizcarra, Valeria; Restrepo-Arbelaez, Daniel; Cardona, Paul; Llano-Piedrahita, Julián; et al. (Frontiers in Human Neuroscience, 2024)
Objective. To analyze patient-reported outcomes, cognitive function, and persistent symptoms in patients with neurologic post-acute sequelae of SARS-CoV-2 infection (Neuro-PASC) in Colombia. Methods. We recruited patients with laboratory-confirmed COVID-19 and persistent PASC symptoms lasting more than six weeks at the CES University and CES Clinic (Medellín, Colombia). We included 50 post-hospitalization Neuro-PASC (PNP) and 50 non-hospitalized Neuro-PASC (NNP) patients. Long-COVID symptoms, cognitive (NIH Toolbox v2.1-Spanish for 18+), patient-reported (PROMIS) outcomes, and relevant medical history were evaluated. Statistical analyses were performed via generalized linear models. Results. Overall, brain fog (60%), myalgia (42%), and numbness or tingling (41%) were the most common neurological symptoms, while fatigue (74%), sleep problems (46%), and anxiety (44%) were the most common non-neurological symptoms. Compared to NNP, PNP patients showed a higher frequency of abnormal neurological exam findings (64% vs. 42%, p = 0.028). Both groups had impaired quality of life (QoL) in domains of cognition, fatigue, anxiety depression and sleep disturbance, and performed worse on processing speed and attention than a normative population. In addition, NNP patients performed worse on executive function than PNP patients (T-score 42.6 vs 48.5, p = 0.012). Persistent PASC symptoms of anxiety and depression were associated with worse QoL and cognitive outcomes. Brain fog and fatigue remained persistent symptoms across all durations of Long COVID. Conclusions. Our findings highlight the high incidence and heterogeneity of the neurologic symptoms and impacts of Long COVID even more than two years from disease onset. Early detection, emotional support and targeted management of Neuro-PASC patients are warranted.